Undergraduate Students' Needs Toward Instructional Material During Pandemic - Nengsih, Yanti Karmila; Nurrizalia, Mega; Waty, Evy Ratna Kartika; Shomedran, Shomedran (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
This study aims to get an overview of student needs for teaching materials during the covid-19 pandemic. The subjects in this study were 47 students of the out-of-school education study program class of 2020/2021. This type of research is descriptive with a qualitative approach. The data in this study were obtained from the results of a questionnaire distributed using a google form that has been provided by the researcher to find out the responses of students of out-of-school education study programs to the need for teaching materials during online lectures during the pandemic. The results obtained from the analysis of student needs for teaching materials during the pandemic are: first, during the pandemic in online lectures, as many as 91.5% of students are more interested in finding references or lecture materials digitally. Second, as many as 66.7% of students stated that the reason for choosing digital teaching materials was that they were practical to use. Third, 100% of students need interesting digital teaching materials. Fourth, as much as 76.6% can increase student motivation in learning. Fifth, for the form of teaching materials needed by students, as many as 82.6% of students need Android-based interactive textbooks because they are easy to access anywhere and easy to understand. This shows that students need teaching materials that support the lecture process during the pandemic, where lectures are conducted online.